Digital Image Correlation (DIC) Technique for Fatigue Crack Growth Analysis Using âˆ†CTOD Criteria - B. Patil, Akshay; P. Toppo, Suraj; RKP Singh, Dr. (International Journal of Engineering and Technology, 2018)
The present paper deals with an experimental determination of fatigue crack growth rate (FCGR) of microalloyed steel (38MnVS6) to study the crack propagation in forged automobile crankshafts. The criterion based on crack tip opening displacement range (âˆ†CTOD) is used to investigate the fatigue crack growth rate. In the current work use of 2D-digital image correlation (DIC) technique for the measurement of crack tip opening displacement (CTOD) and crack length (a) is proposed. Digital Image Correlation (DIC) is a full field displacement and strain measurement technique. It is easier to measure the crack tip opening displacement (CTOD) and crack length (a) with this technique than other. Fatigue crack growth curve based on crack tip opening displacement (CTOD) criteria is presented using DIC.Â Â